Durabilitas Blok Beton Sandwich dengan Isian Styrofoam di Lingkungan Agresif - Aditya Kenanga; M Rizky Darmawan; Rr.M.I Rretno Susilorini; David Widianto (Universitas Katolik Soegijapranata Semarang, 2017)
The research aimed to observe durability of sandwich concrete block with styrofoam inaggressive environment which was modeled by curing media. The curing media used in thisresearch are plain water, sea water, brakish water, and tidal flooding water. The curing wasconducted for 28 days and followed by compressive strength test. The result of this researchfound that maximum compressive strength was 1,76 MPa with tidal flooding water as curingmedia, followed by 1,67 MPa with brakish water as curing media, and also 1,64 MPa with seawater as as curing media, and the lowest compressive strength was 1,36 MPa with plain wateras as curing media.